2019
DOI: 10.1002/jgc4.1182
|View full text |Cite
|
Sign up to set email alerts
|

Translating genomic testing results for pediatric critical care: Opportunities for genetic counselors

Abstract: Genomic sequencing (GS), such as whole genome and exome sequencing, is rapidly being integrated into pediatric critical care settings. Results are being used to make high impact decisions including declarations of futility, withdrawal of care, and rationing of scarce resources. In this qualitative study, we conducted interviews with clinicians involved in the care of critically ill children with congenital heart disease (CHD) to investigate their views on implementation of GS into clinical practice. Interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 47 publications
1
14
1
Order By: Relevance
“…All professional groups valued cross-discipline collaborative working when delivering RGS, highlighting the benefits of multidisciplinary team meetings to triage patients and interpret results. As with other studies in acute [ 18 ] and more routine settings [ 20 , 35 , 36 ], we noted that as GS moves to mainstream clinical practice [ 37 ], a growing role for non-genetic professionals was recognised. Additional training is needed alongside support from genetics colleagues for decisions on eligibility, interpretation of results and counselling.…”
Section: Discussionsupporting
confidence: 74%
“…All professional groups valued cross-discipline collaborative working when delivering RGS, highlighting the benefits of multidisciplinary team meetings to triage patients and interpret results. As with other studies in acute [ 18 ] and more routine settings [ 20 , 35 , 36 ], we noted that as GS moves to mainstream clinical practice [ 37 ], a growing role for non-genetic professionals was recognised. Additional training is needed alongside support from genetics colleagues for decisions on eligibility, interpretation of results and counselling.…”
Section: Discussionsupporting
confidence: 74%
“…These concerns are J o u r n a l P r e -p r o o f consistent with the views expressed in prior studies. 12,13 However, we did not see as strong a preference for a genetic-led service as reported in another prior study, 14 perhaps because intensive care clinicians developed confidence as effective training and reliable and timely genetics service support were available in the Project Baby Bear sites. Conversely the removal of a requirement for "suspicion of a genetic disorder" in favor of criteria-based testing may have allayed some of the fears of the intensive care clinicians in determining patient eligibility for rWGS testing.…”
Section: Discussioncontrasting
confidence: 68%
“…9 The studies of clinician attitudes and beliefs about genomic sequencing reveal concerns about lack of provider knowledge about appropriate use of the technology, desire for greater support from genetics specialists and concerns about consequences for patients and families about future use of the genomics results. 6,[12][13][14] A large scale quality improvement project implementing rWGS, Project Baby Bear, was funded by California Medicaid (Medi-Cal) and included five tertiary children's hospitals across the state serving rural and urban populations with California Children's Services accredited regional NICUs and PICUs. Rather than requiring clinical suspicion of a genetic disorder, J o u r n a l P r e -p r o o f criteria-based enrollment was used.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Deuitch et al. (2020) demonstrated that non‐genetics clinicians desire genetic specialists like genetic counselors to help in inpatient settings, as the clinicians feel they lack expertise in genetic test result interpretation. Much like genetic counselors are employed in outpatient subspecialty clinics, genetic counselors can work in inpatient subspecialties and educate non‐genetics providers on genetic counseling and testing.…”
Section: Discussionmentioning
confidence: 99%